2014
DOI: 10.5811/westjem.2014.9.22569
|View full text |Cite
|
Sign up to set email alerts
|

Management of In-Flight Medical Emergencies: Are Senior Medical Students Prepared to Respond to this Community Need?

Abstract: IntroductionIn-flight medical emergencies on commercial aircraft are common in both domestic and international flights. We hypothesized that fourth-year medical students feel inadequately prepared to lend assistance during in-flight medical emergencies. This multicenter study of two U.S. medical schools obtains a baseline assessment of knowledge and confidence in managing in-flight medical emergencies.MethodsA 25-question survey was administered to fourth-year medical students at two United States medical scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…A selfreported questionnaire was used, consisting of questions on demographic information, knowledge of in-flight medicine and confidence in managing IMEs. The questionnaire was developed using a combination of literature review, guidelines on aviation medicine and a previous questionnaire by Katzer et al (1,2,7,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) The questionnaire underwent face and content validation to improve its relevance and clarity. The expert panel for content validation included a primary care medicine lecturer, two emergency physicians and three doctors specialising in aviation medicine.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A selfreported questionnaire was used, consisting of questions on demographic information, knowledge of in-flight medicine and confidence in managing IMEs. The questionnaire was developed using a combination of literature review, guidelines on aviation medicine and a previous questionnaire by Katzer et al (1,2,7,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) The questionnaire underwent face and content validation to improve its relevance and clarity. The expert panel for content validation included a primary care medicine lecturer, two emergency physicians and three doctors specialising in aviation medicine.…”
Section: Methodsmentioning
confidence: 99%
“…In-flight medical emergencies (IMEs) have been reported to occur at a rate of one in 604-753 flights. (1,2) Passenger doctors are often roped in to provide help during IMEs, in 43%-85% of reported incidents. (1,3,4) Other studies on Good Samaritan acts by doctors showed that an airplane flight is a common setting for such acts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A multicenter survey of fourth-year medical students found that on average they felt unprepared to respond to in-flight emergencies. 3 Unfortunately, there are no standard curricula to bridge this known knowledge gap. Therefore, the majority of residents likely feel a similar unease when responding to an in-flight emergency.…”
Section: Introductionmentioning
confidence: 99%
“…8 Notwithstanding the increasing occurrence of in-flight emergencies, many medical professionals are unfamiliar with the liability and the associated medico-legal issues of providing assistance in these types of situations. 9 Although provisions exist in theory about good Samaritans on the ground, 10 it…”
Section: Introductionmentioning
confidence: 99%